Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve this step-by-step:
### Step 1: Determine \(fog(x)\)
We are given two functions:
1. \( f(x) = x - 1 \)
2. \( g(x) = 2x + 1 \)
To find \( fog(x) \), which means \(f(g(x))\), we need to substitute \(g(x)\) into \(f(x)\):
[tex]\[ f(g(x)) = f(2x + 1) \][/tex]
Now, apply the function \(f\) to \(2x + 1\):
[tex]\[ f(2x + 1) = (2x + 1) - 1 \][/tex]
[tex]\[ f(2x + 1) = 2x \][/tex]
Therefore, \( fog(x) = 2x \).
### Step 2: Calculate \(fog(2)\)
Now we need to evaluate \(fog(2)\):
[tex]\[ fog(2) = 2 \times 2 \][/tex]
[tex]\[ fog(2) = 4 \][/tex]
### Step 3: Find \(k\) when \( h(x) = 2x + 3 \) and \( f^{-1}(7) = k \)
Given the function:
[tex]\[ h(x) = 2x + 3 \][/tex]
We need to find the value of \(x\) when \(h(x) = 7\):
[tex]\[ 2x + 3 = 7 \][/tex]
Subtract 3 from both sides:
[tex]\[ 2x = 4 \][/tex]
Divide by 2:
[tex]\[ x = 2 \][/tex]
Therefore, \( k = 2 \).
### Summary
- The composite function \( fog(x) = 2x \) and \( fog(2) = 4 \).
- The value of \( k \) such that \( f^{-1}(7) = k \) for the function \( h(x) = 2x + 3 \) is \( k = 2 \).
So the final results are:
[tex]\[ \text{fog}(2) = 4 \][/tex]
[tex]\[ k = 2 \][/tex]
### Step 1: Determine \(fog(x)\)
We are given two functions:
1. \( f(x) = x - 1 \)
2. \( g(x) = 2x + 1 \)
To find \( fog(x) \), which means \(f(g(x))\), we need to substitute \(g(x)\) into \(f(x)\):
[tex]\[ f(g(x)) = f(2x + 1) \][/tex]
Now, apply the function \(f\) to \(2x + 1\):
[tex]\[ f(2x + 1) = (2x + 1) - 1 \][/tex]
[tex]\[ f(2x + 1) = 2x \][/tex]
Therefore, \( fog(x) = 2x \).
### Step 2: Calculate \(fog(2)\)
Now we need to evaluate \(fog(2)\):
[tex]\[ fog(2) = 2 \times 2 \][/tex]
[tex]\[ fog(2) = 4 \][/tex]
### Step 3: Find \(k\) when \( h(x) = 2x + 3 \) and \( f^{-1}(7) = k \)
Given the function:
[tex]\[ h(x) = 2x + 3 \][/tex]
We need to find the value of \(x\) when \(h(x) = 7\):
[tex]\[ 2x + 3 = 7 \][/tex]
Subtract 3 from both sides:
[tex]\[ 2x = 4 \][/tex]
Divide by 2:
[tex]\[ x = 2 \][/tex]
Therefore, \( k = 2 \).
### Summary
- The composite function \( fog(x) = 2x \) and \( fog(2) = 4 \).
- The value of \( k \) such that \( f^{-1}(7) = k \) for the function \( h(x) = 2x + 3 \) is \( k = 2 \).
So the final results are:
[tex]\[ \text{fog}(2) = 4 \][/tex]
[tex]\[ k = 2 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.